A Bibliometric Analysis of Sustainability in MSME - Deepshikha Patel; Chandra Bhooshan Singh (PT Agung Media Publisher, 2024)
This research paper examines the role of Micro, Small, and Medium Enterprises (MSMEs) in the Indian economy and their sustainability. It analyses 85 Scopus documents from 66 sources between 2014 and 2024, revealing a peak in scientific production in 2023. The study emphasizes the importance of sustainable practices for long-term success. This comprehensive research paper rigorously examines the pivotal role of Micro, Small, and Medium Enterprises (MSMEs) in the Indian economy and emphasizes the critical importance of sustainable practices for long-term success. Through meticulous analysis of 85 Scopus documents from 66 sources between 2014 and 2024, the study conclusively reveals a peak in scientific production in 2023 and robust ties between India and various other countries in this domain.